CD4 binding determinant mimicry for HIV vaccine design - NISHIYAMA, YASUHIRO; Planque, Stephanie A.; Hanson, Carl V.; Massey, Richard J.; Paul, Sudhir (Frontiers in Immunology, 2012)
The immunodominant epitopes expressed by the HIV-1 envelope protein gp120 are hypermutable, defeating attempts to develop an effective HIV vaccine. Targeting the structurally conserved gp120 determinant that binds host CD4 receptors (CD4BD) and initiates infection is a more promising route to vaccination, but this has proved difficult because of the conformational flexibility of gp120 and immune evasion mechanisms used by the virus. Mimicking the outer CD4BD conformational epitopes is difficult because of their discontinuous nature. The CD4BD region composed of residues 421-433 (CD4BDcore) is a linear epitope, but this region possesses B cell superantigenic character. While superantigen epitopes are vulnerable to a small subset of spontaneously-produced neutralizing antibodies present in humans without infection (innate antibodies), their noncovalent binding to B cell receptors (BCRs) does not stimulate an effective adaptive response from B cells. Covalent binding at naturally-occurring nucleophilic sites of the BCRs by an electrophilic gp120 analog (E-gp120) is a promising solution. E-gp120 induces the synthesis of neutralizing antibodies the CD4BDcore. The highly energetic covalent reaction is hypothesized to convert the abortive superantigens-BCR interaction into a stimulatory signal, and the binding of a spatially distinct epitope at the traditional combining site of the BCRs may furnish a second stimulatory signal. Flexible synthetic peptides can detect pre-existing CD4BDcore-specific neutralizing antibodies. However, induced-fit conformational transitions of the peptides dictated by the antibody combining site structure may induce the synthesis of non-neutralizing antibodies. Successful vaccine targeting of the CD4BD will require a sufficiently rigid immunogen that mimic the native epitope conformation and bypasses B cell checkpoints restricting synthesis of the neutralizing antibodies.